Molluscum contagiosum inside fibrous papilloma. - Milano, A. (European Journal of Pediatric Dermatology, 2016)
Molluscum contagiosum is a viral infection that affects the first years of life; the infection subsides spontaneously in about a year when the organism processes specific defenses against the virus that consequently disappears from the body; the infection usually confers lifelong immunity (1). The peculiarity of this case is the presence of a typical molluscum contagiosum within a fibrous epithelial structure; despite having tried to dissect the piece otherwise we could not find a connection with the epidermis covering the fibrous papilloma. We searched in the relevant literature for similar cases but we did not find anything. We only found a few cases of cysts located inside the dermis and containing molluscum contagiosum bodies both in the central keratin and focally in the cyst wall itself; even in these cases the virus infected cyst was within the dermis and covered by normal epidermis (2).